URGENSI PENERAPAN SISTEM CYBER NOTARY DITENGAH PANDEMI COVID 19 - Tamara Dwi Rizki Amanda; Wardani Rizkianti (Fakultas Hukum Universitas Islam Malang, 2021)
Indonesia has designated the Covid-19 pandemic as a disease that causes a public health emergency and the government has issued several regulations requiring people to work from home. This research covers two main problemsÂ Â First, how is the validity of notary deeds made by the cyber notary system? Second, what is the urgency of implementing a cyber notary system amid the Covid-19 pandemic? This writing uses normative juridical research. Notary deeds made by cyber notary have the power of proof as underhand deeds. The importance of implementing cyber notary amid a pandemic is strengthenedÂ one of which is the Minister of Health Regulation Number 9 of 2020 and Government Regulation Number 21 of 2020 which requires closing the office sector and working from home to break the line of the spread of the coronavirus in Indonesia.